Kosmu Sebagai Sistem Manajemen Kos Griya Muallimah - Dian Nur Hayati; Maryam Maryam (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Information processing is currently greatly facilitated by the role of technology, so that it can be utilized in various sectors including temporary housing management. Kos Griya Muallimah is a boarding house specifically for women. Kos Griya Muallimah in its data management currently still uses a manual method, which is recorded in a book. The creation of KosMu can help Kos Griya Muallimah owners manage boarding house data more regularly and efficiently. This study aims to manage boarding house resident data, room data, payment confirmation data, and complaint data from Kos Griya Muallimah residents to be computerized so as to reduce human error, increase accuracy, and ease in finding the data needed. The development method used in this study is the prototype method. The prototype method is used so that developers can interact with users during website creation so that users can provide input and opinions regarding the website being developed. The system has been tested with Black Box testing to find out the system runs according to user expectations, the results of the features, menus, and buttons run well and based on usability testing with the System Usability Scale (SUS), a score of 74.5 was obtained, which means that the system is well received by users.